2011
DOI: 10.5762/kais.2011.12.2.795
|View full text |Cite
|
Sign up to set email alerts
|

Factors Related to Quality of Life in the Rural Elderly People Affiliated with Long-term Care Insurance Services

Abstract: This study was performed to determine the levels of quality of life(QOL) according to the grade of long-term care service in the elderly people who affiliated from long-term care insurance, and to reveal its association with socio-demographic characteristics, health status and health related behaviors. The interviews were performed, during the period from March 1st, to May 31th, 2009, to 410 elderlies in rural areas. As a results, the levels of QOL were lower in the group of higher grade of long-term care insu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 12 publications
3
6
0
Order By: Relevance
“…Most of the people who decided the admission of the older adults to the facility were their children and spouses, and most of the people who paid for the stay of the older adults in the facility were their children and the elderly themselves. This was similar to the study results of Shin et al [ 11 ] and Kang et al [ 9 ]. It was found that the decision maker and payer for the Korean older adults residing in nursing homes were mostly the children of the elderly.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Most of the people who decided the admission of the older adults to the facility were their children and spouses, and most of the people who paid for the stay of the older adults in the facility were their children and the elderly themselves. This was similar to the study results of Shin et al [ 11 ] and Kang et al [ 9 ]. It was found that the decision maker and payer for the Korean older adults residing in nursing homes were mostly the children of the elderly.…”
Section: Discussionsupporting
confidence: 93%
“…The mean depression score was higher than 8 points in both groups, thereby indicating that the older adult participants were in a depressed state. This result was similar to those of the previous studies [ 11 , 25 ], thereby suggesting that the older adults participants were depressed due to their relocation to the nursing homes, stress from unfamiliar surroundings, and reduced intimacy with their family members [ 9 , 24 ]. Life satisfaction was slightly higher than the median of 50 in both groups, thereby showing a different result when compared with the previous study [ 26 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“… RFS recommended food score, BDI beck depression inventory, BAI beck anxiety inventory, WHOQOL The World Health Organization quality of life assessmentSubjects were dichotomized into 2 groups according to the presence of depression (BDI ≥16 scores [42, 45]) and anxiety (BAI ≥22 scores [37, 46]) and the median value of WHOQOL-BREF (QoL < 82 points [47])Model 1 adjusted for ageModel 2 additionally adjusted BMI, marital state, smoking, drinking, physical activity, and diagnosis of one or more chronic disease…”
Section: Resultsmentioning
confidence: 99%
“…Multiple linear regression analysis was used to investigate the associations between the RFS and depression, anxiety, and QoL after adjusting for covariates. Subjects were dichotomized into two groups according to the presence of depression (BDI, yes: score ≥ 16; no: score < 16 [42, 45]) and anxiety (BAI, yes: score ≥ 22; no: score < 22 [37, 46]), and the WHOQOL-BREF was divided into two groups using the median (QoL score below the median: < 82 points; QoL score above the median: ≥82 points [47]) since there was no specific criterion. A general linear model was used to analyze the differences in RFS values among the two groups after adjusting for covariates.…”
Section: Methodsmentioning
confidence: 99%